Cote D'Ivoire : Eighth Review Under the Extended Credit Facility Arrangement-Press Release; Staff Report; and Statement by the Executive Director for Cote D'Ivoire. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2015)
This paper discusses Cote d'Ivoire's Eighth Review Under the Extended Credit Facility (ECF) Arrangement. The macroeconomic outlook remains strong with high projected growth rates supported by sustained improvements in the business climate and rising private investment, including in large private-public infrastructure projects. Risks to the near-term growth outlook are moderately tilted to the downside. Adverse weather owing to El Nino could lower output, and the failure to contain fiscal risks could weaken the fiscal accounts. The IMF staff supports the authorities' request for completion of the eighth ECF review.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet